Asymmetry in Leader Image Effects and the Implications for Leadership Positioning in the 2010 British General Election - Mortimore, Roger; Baines, Paul R.; Crawford, Ian; Worcester, R.; Zelin, Andrew (Warc, 2013)
Using national survey data on voters' perceptions of party leaders during the 2010 British general election campaign, we use logistic regression analysis to explore the association between specific image attributes and overall satisfaction for each leader. We find attribute-satisfaction relationships differ in some respects between the three main party leaders, demonstrating that leader image effects are not symmetrical across leaders. We find evidence that negative perceptions have more powerful effects on satisfaction than positive ones, implying that parties should seek to determine a leader's image attribute perceptions measured against the public's expectations of them on the same dimensions. The positions that campaigners ought then to choose are those that will have the most beneficial effect in encouraging voting behaviour for each particular leader or discouraging voting behaviour for an opponent.